On the Duty of Civil Disobedience - Thoreau, Henry David, 1817-1862 (Salt Lake City, UT : Project Gutenberg, 1993)
"On the Duty of Civil Disobedience" by Henry David Thoreau is an essay first published in 1849. Thoreau argues that individuals must follow their conscience over unjust laws, challenging the idea that citizens should passively obey government authority. Motivated by his opposition to slavery and the Mexican-American War, he contends that governments often enable injustice rather than prevent it. The essay became a foundational text for nonviolent resistance, profoundly influencing activists like Mahatma Gandhi and Martin Luther King Jr. in their struggles for justice and social change. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Civil_Disobedience_(Thoreau)
Release date is 1993-06-01
Sameer Parekh
Keywords: Civil disobedience; Government, Resistance to